Stability and release of peach polyphenols encapsulated by Pickering high internal phase emulsions in vitro and in vivo. (May 2023) - Song, Yu; Zhou, Leyi; Zhang, Decai; Wei, Yingying; Jiang, Shu; Chen, Yi; Ye, Jianfen; Shao, Xingfeng
Abstract: In this work, Pickering high internal phase emulsions (HIPEs) were employed to protect peach polyphenols in vitro and vivo . Firstly, HIPEs stabilized by zein nanoparticles and gum Arabic (GA) with corn oil volume fraction of 76% were prepared. The effects of pH in aqueous phase (pH 3–7) and GA concentration (0 %–4%) on the creaming index (CI), particle size, potential, microstructure and rheology of HIPEs were analyzed. Results indicated that after GA concentration reached 2%, the stability of HIPEs kept relatively steady. With the decrease of pH in aqueous phase, the stability of HIPEs improved. Consequently, the pH 3 and 2% GA concentration were selected to prepare the stable HIPEs. Secondly, the HIPEs with corn oil dissolved peach polyphenols (PP-HIPEs) were obtained and the encapsulation rate of peach polyphenols reached 74.25%. Compared to polyphenols dissolved in water and corn oil, the stability of peach polyphenols in PP-HIPEs during UV irradiation, storage and heating significantly improved. Bioaccessibility of peach polyphenols in PP-HIPEs during simulated gastrointestinal digestion obviously enhanced and reached 60.49%. The content of polyphenols in stomach, small intestine, colon and feces in PP-HIPEs were higher, suggesting the better protection, higher adsorption and stronger potential biological activity during digestion. Meanwhile the peach polyphenols could prevent the increase of body weight caused by HIPEs. Thus, the HIPEs could be used as an excellent protective and effective delivery method for peach polyphenols during digestion. Graphical abstract: Image 1 Highlights: The encapsulation rate of peach polyphenols in HIPEs (PP-HIPEs) reached 74.25%. Peach polyphenols in the PP-HIPEs could well resist UV irradiation, storage and heating. Bioaccessibility of peach polyphenols in PP-HIPEs reached 60.49% in vitro digestion. Polyphenols in PP-HIPEs exhibited better adsorption and release in vivo digestion. Peach polyphenols could prevented the increase of mice body weight caused by HIPEs.